2008
DOI: 10.1159/000140974
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Azathioprine and 6-Mercaptopurine in Japanese Pediatric Patients with Ulcerative Colitis: A Survey of the Japanese Society for Pediatric Inflammatory Bowel Disease

Abstract: Background and Aims: Azathioprine (AZA) and 6-mercaptopurine (6-MP) have recently been used in Japanese pediatric patients with ulcerative colitis. The aims of this study were to evaluate both the therapeutic efficacy and safety of AZA/6-MP in this group of patients. Methods: Fourteen members of the Japanese Society for Pediatric Inflammatory Bowel Disease reported 35 retrospective cases that received AZA/6-MP and were evaluated for adverse drug effects. In those who tolerated AZA/6-MP, disease activity and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
(19 reference statements)
0
21
0
3
Order By: Relevance
“…Hepatitis was reported in 2 patients (10%) and leukopenia was reported in 1 patient (5%). Tajiri et al [11] reported that 14 patients (40%) of 35 UC patients experienced adverse drug effects to AZA or 6-MP treament in a study conducted in Japan. Leukopenia was reported reported in 11 patients (27.5%), aplastic anemia in 1 patient (2.5%), pancreatitis in 1 patient (2.5%) and liver dysfunction in 1 patient (2.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis was reported in 2 patients (10%) and leukopenia was reported in 1 patient (5%). Tajiri et al [11] reported that 14 patients (40%) of 35 UC patients experienced adverse drug effects to AZA or 6-MP treament in a study conducted in Japan. Leukopenia was reported reported in 11 patients (27.5%), aplastic anemia in 1 patient (2.5%), pancreatitis in 1 patient (2.5%) and liver dysfunction in 1 patient (2.5%).…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a higher rate of adverse events in Asians compared with Caucasians prescribed thiopurines, particularly bone marrow suppression in up to 40% of Asian subjects 193,194 . Thiopurine methyltransferase (TPMT) polymorphisms alone may not be responsible for the development of toxicity in Asian patients 194,195 .…”
Section: Medical Therapymentioning
confidence: 99%
“…Azathioprine and 6‐MP are considered equivalent in efficacy at the equivalent doses. A survey of the efficacy and safety of AZA/ 6‐MP in a Japanese pediatric population with UC found that 40% developed adverse drug effects including aplastic anemia, leukopenia and hepatotoxicity 155 . Lower starting doses in Asian compared to Caucasian populations along with close monitoring of complete blood count and liver function is recommended 156 .…”
mentioning
confidence: 99%